PENERAPAN METODE PEMBELAJARAN MODELING DALAM MENINGKATKAN KEMAMPUAN MENULIS KARANGAN SISWA V SEKOLAH DASAR - Sri Muslihah (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Indonesian language, has three aspects that need to be considered, namely aspects of knowledge (competence), skills and attitudes. Those three aspects are in succession concerning the four skills, namely listening, speaking, reading, and writing. The research method used in this study is a descriptive quality research method. With the study subject of students and teachers of class V MI Diponegoro 03 Karangklesem District South Purwokerto. The analysis of the data used is a thematic technique of analysis by analyzing the data in the form of field records, recordings, documents and interviews results in depth. The result of this study is that the presence of models in learning essay writing material will help students to think critically. Students will be assisted by observing the model provided, so that students better understand the material being taught. Students not only receive information from teachers, but students can also dig into the information of the model provided.